2015
DOI: 10.1111/medu.12822
|View full text |Cite
|
Sign up to set email alerts
|

‘It was serendipity’: a qualitative study of academic careers in medical education

Abstract: Bourdieu's theory provides insight into medical educator career paths and the positioning of medical education within medical schools. Medical educators have an indistinct practice, and limited cultural capital in the form of research outputs. In order to maintain and strengthen their careers, educators must create alternative sources of capital, through fostering collaborative alliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 33 publications
(46 reference statements)
4
104
0
1
Order By: Relevance
“…This resentment towards promotion assessment against a metric that did not relate to teaching quality was also reported by early career medical educators in Australian and New Zealand medical schools [10] and clinicians engaged in an academic careers [12, 13], suggesting a worldwide phenomenon.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This resentment towards promotion assessment against a metric that did not relate to teaching quality was also reported by early career medical educators in Australian and New Zealand medical schools [10] and clinicians engaged in an academic careers [12, 13], suggesting a worldwide phenomenon.…”
Section: Discussionmentioning
confidence: 71%
“…As with any new field of scholarly activity medical education faces multiple challenges such as low levels of funding, lack of recognition and reduced opportunities for career development [10, 13, 15, 35]. The participants mentioned that their efforts are undervalued and under-supported financially in comparison with those working in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors findings in medical education, where medical educators have been argued to have less cultural capital in relation to their clinical research colleagues (citing less respect and financial support); referring to medical education as the 'Cinderella discipline'. 27 Similarly, research by Albert and colleagues 28 identified that the majority of biomedical health researchers exhibited a predominantly negative posture toward social science researchers, where education research arguably fits. 29 Methodological challenges and strengths Unfortunately, inclusion of the patient voice in our study was limited.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Experienced GPs and their ability to formulate management plans in response to a myriad of conflicting problems and contextual factors is invaluable given that clinical guidelines are usually acontextual, relate to single conditions and can have contradictory recommendations, 9 thereby creating difficulty for trainees who need to learn to manage the undifferentiated, multimorbid and complex presentations that characterise much of general practice care. 8,10 Supervisors are not (yet) easily replaced by electronic information sources at the point of care, but understanding the different genres within these ad hoc learning encounters and learning how to adapt to the genre at play, will ensure that we do not miss the boat in providing maximal learning and ultimately better health care for the patients whom we serve. The struggle to support the transition to medical educator…”
mentioning
confidence: 99%